(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2019)
The article will present selected issues in the field of survey research and its potential, which contributes to the development of social opinion research techniques. This technique allows the individual to get to know the opinion of others regarding a proper matter. The applied research methods are a review of the current literature on the subject and analysis of selected studies. The use of the survey method was presented on the example of a consumer based on California State University Long Beach 2007 research about consumers of the 21st century, Social Diagnosis Report 2015 and Public Opinion Research Center (CBOP): Confidence in politicians in July 2018.